INTESTINAL INVOLVEMENT IN SYSTEMIC SCLERODERMA - Madiyorov Sh.E.,; Sagatova D.R. (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Systemic scleroderma (SSc) is a multifaceted autoimmune disorder marked by fibrosis in the skin and internal organs. Gastrointestinal (GI) tract involvement ranks as the second most prevalent feature after skin changes, affecting up to 90% of patients. In particular, small and large intestine manifestations are critical, occurring in 40-70% of cases, leading to dysmotility, malabsorption, and severe morbidity. These include small intestinal bacterial overgrowth (SIBO), pseudo-obstruction, and malnutrition, which contribute significantly to reduced quality of life and elevated mortality rates. The pathogenesis involves vascular damage, smooth muscle atrophy, and neural dysfunction, exacerbated by fibrosis and inflammation. This thesis explores the pathogenesis, clinical presentations, diagnostic approaches, and therapeutic strategies for intestinal involvement in SSc. The aim is to assess current scientific insights and propose innovative management protocols. Findings indicate SIBO in 30-60% of patients, often linked to hypomotility and a 50% mortality risk from malnutrition. Disease progression is driven by endothelial dysfunction, platelet activation, and cytokine overexpression like IL-6. Management relies on prokinetics and antibiotics, but emerging therapies such as fecal microbiota transplantation (FMT) and neuromodulation show promise. The thesis provides recommendations for early detection and multidisciplinary care in SSc patients, considering genetic variations and microbiome alterations.